When Civilisation Reached America: Colonial Readings Driven by the CSIC During Franco’s Regime (1940-1975) - Fernández Gallego, Alba (Hispania Nova, 2023)
This study examines the position adopted by the CSIC regarding Ibero-America in its historiographical practice, a faithful reflection of the rupture with the previous period and the imposition of the idea of Hispanidad. Together with administrative sources, the monographs published by the Instituto Gonzalo Fernández de Oviedo and the Escuela de Estudios Hispano-Americanos, as well as their periodical publications during the 1940s and 1950s, are the main sources analysed. These offer a picture of the interpretation offered by CSIC historians of this past, which is structured along four axes: the moments of conquest and discovery, within the framework of Spain’s so-called civilising mission; the construction of the “other”, based on the indigenous element; missionary activity; and the anthropological vision.
Keywords: francoism; CSIC; americanism; historiography; hispanidad